Simplified solution for tunnel-soil-pile interaction in Pasternak’s foundation model - Zhang, Zhiguo; Huang, Maosong; Xu, Chen; Jiang, Yunjuan; Wang, Weidong (Tunnelling and underground space technology, 2018)
•Pasternak’s model is applied considering the shearing deformation of foundation.•The proposed method is to overcome the drawback of plane strain analyses.•A parametric analysis is performed to discuss the influencing factors.•The results in this study are closer to monitoring data and centrifuge test data. The current design practice for predicting the interaction mechanics for tunnel-soil-pile is generally based on Winkler’s foundation, which is subject to some important limitation, such as ignoring the continuity of the soil foundation. Furthermore, the current analytical studies are mostly employed the plane strain analyses and do not consider the influences of lateral soil displacements on pile behaviour. To improve the accuracy for the pile behaviour prediction induced by tunnelling, the analytical method should account for the effects of a number of parameters, such as the ground shearing displacements, and the influence of lateral soil displacements next to the pile. This paper focuses on a simplified solution based on Pasternak’s foundation model to predict the lateral displacements and internal forces of a single-pile and group-piles induced by tunnelling considering the effects of lateral soil displacements. First, the simplified solution of tunnel-soil-pile interaction, which reflects the influence of shearing displacements of foundation, is established on Pasternak’s foundation model. Second, the equivalent concentrated forces are supplied to the pile through the shear layer to consider the influence of lateral soils beside the pile. The validity of the solutions is verified by the boundary element program results, centrifuge test data, and field measurements. The calculated results are also compared with and without considering the effects of tunnel-soil-pile interaction. When the influences of lateral soil displacements are considered, the results are shown to be closer to the monitored in-situ data and the centrifuge test data. In addition, the influencing factors of a single-pile and group-piles displacements are also investigated, including the shear layer modulus, pile diameter, ground-loss ratio, pile-tunnel distance, and pile spacing. The influence of soil shear displacements on pile response cannot be ignored, and an error may occur when Winkler’s foundation model is used to solve this problem.